2016
DOI: 10.3892/mmr.2016.5394
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-155 sensitizes lung cancer cells to irradiation via suppression of HK2-modulated glucose metabolism

Abstract: Abstract. MicroRNAs (miRNAs) are small non-coding regulatory RNAs, which are involved in the post-transcriptional regulation of gene expression. miRNA (miR)-155, which has previously been reported to be overexpressed in lung cancer, is correlated with poor patient prognosis. The present study aimed to investigate the effects of miR-155 on the radiosensitivity of human non-small cell lung cancer (NSCLC) cells. To explore the roles of miRNAs in the regulation of irradiation sensitivity of human lung cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The expression of HK2 in cancer cells could be regulated at the transcriptional and post-transcriptional level. Previous studies showed that HK2 was directly regulated by miR-199a-5p in liver cancer 38 ; by miR-155 in lung cancer 39 ; and by miR-143 in colon cancers 40 . Zhuo et al revealed that PI3K/Akt signaling inhibited cell apoptosis and promoted tumor growth by upregulating HK2 expression in pediatric osteosarcoma 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HK2 in cancer cells could be regulated at the transcriptional and post-transcriptional level. Previous studies showed that HK2 was directly regulated by miR-199a-5p in liver cancer 38 ; by miR-155 in lung cancer 39 ; and by miR-143 in colon cancers 40 . Zhuo et al revealed that PI3K/Akt signaling inhibited cell apoptosis and promoted tumor growth by upregulating HK2 expression in pediatric osteosarcoma 41 .…”
Section: Discussionmentioning
confidence: 99%
“…5m ). A previous report showed miR-155/143 controls HK2 via STAT3 or C/EBP beta [ 10 ], and a recent report also showed that miR-155 control HK2 expression in NSCLC [ 22 ]. Another study using knockout mice showed that the loss of miR-155 confers insulin resistance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs serve key roles in the regulation of glucose metabolism in cancer cells (20,21). As an oncogenic miRNA, miRNA-10a is upregulated in lung cancer (14); however, to the best of our knowledge, its expression pattern in OSCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%